Histological findings after non-ablative Er:YAG laser therapy in women with severe vaginal atrophy. (19th October 2020) - Gaspar, A.; Silva, J.; Calderon, A.; Di Placido, V.; Vizintin, Z.
Abstract: Objective: The aim of this study was to evaluate the effect of non-ablative erbium vaginal laser treatment on vaginal mucosa tissue affected by severe atrophy. Methods: Ten patients with severe genitourinary syndrome of menopause were treated with two sessions of the non-ablative erbium-doped yttrium aluminium garnet laser (Er:YAG laser) separated by 4 weeks. Vaginal biopsies were performed before and 3 months after the second treatment. The improvement in vaginal atrophy was assessed using multiple measuring tools before and 6 months after the treatment. The degree of patients' satisfaction was also assessed. Results: Microscopic examination showed significant changes in the main structural components of the vaginal wall mucosa after two non-ablative Er:YAG laser sessions. The epithelial thickness increased from 45 µm (10–106 µm) to 153 µm (97–244 µm) measured 3 months after the final laser treatment. Vaginal atrophy improved in all patients by all measured outcomes. The degree of patient satisfaction was very high (3.6 on the Likert four-point scale). No adverse events or complications were observed in any of the sessions. Conclusion: The non-ablative Er:YAG laser seems to be a safe and effective method to increase epithelial thickness of the vaginal mucosa in patients with severe vaginal atrophy.